Topical Antibiotics Without Wound Dressing After Circumcision to Prevent Post-Surgical Infection: Serial Case Report - Rachmanio, Nicko; Fredianto, Meiky; Shobastian, Wahyu Derajat (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Treatment of post-circumcision wounds usually uses tulle and gauze to prevent bleeding and infection. Treatment of advanced wounds in the form of removing the attached gauze causes a feeling of insecurity in the patient because the pain caused by the gauze becomes stuck with an injury that has not healed and often causes bleeding. Antibiotic ointments have been studied to act as a barrier instead of gauze to protect against contamination and keep moisture. It is hoped that using antibiotic ointments without gauze pads can prevent the formation of post-circumcision infection and prevent pain when removing the gauze. Method: Observations were made on eight children aged 7 to 15 years who underwent mass circumcision at PKU Muhammadiyah Gamping Yogyakarta and wound care using only the antibiotic chloramphenicol ointment after circumcision without using gauze. Detailed wound care instructions are given to sufferers and their families at home post-surgery. Monitoring and dialogue through online media are carried out if problems arise during wound treatment. Assessments were carried out daily by sending pictures of wounds via online media until five days after circumcision. Result: From the results of observations, one patient with surgical wound inflammation based on the ASEPSIS score was categorized as having "impaired healing," and seven other patients did not experience post-circumcision inflammation with wound treatment using only chloramphenicol antibiotic ointment. The risk aspect found in this patient as an infectious etiology is the early age, which is difficult in treating wounds coupled with the treatment of wounds carried out by non-professional personnel. Conclusion: Topical antibiotic chloramphenicol without wound dressings can be an option for maintaining post-circumcision wounds.